Beyond Borders: Do Gender Norms and Institutions Affect Female Businesses? - Holger Görg; Ina C. Jäkel (Institute of Labor Economics (IZA), 2024)
In this paper, we investigate whether gender norms and institutions act as a constraint to the performance of female businesses. We exploit novel and unique micro data on start-ups in Denmark, which we combine with information on individual-level characteristics of the entrepreneur as main decision maker of the firm. We overcome the challenge of disentangling norms and institutional biases against women from other constraints and hurdles that female businesses might face by exploiting detailed trade data. In this trade context, we study the relative performance of firms across markets with varying institutions, while controlling for other factors that affect female businesses uniformly across all markets. We provide evidence that gender inequality and institutional biases against women in trade partner countries play an important role in explaining gender differences in export and import behaviour. We also perform an event study of a concrete policy change in a destination market – the introduction of quotas for the share of females on the boards of directors in Norway – and how it has affected the gender gap in trade participation.
Keywords: F14; J16; M13; 330; gender inequality; firm internationalization; start-up performance